The most important factors affecting the improvement of communication between the physical education and sports teacher and primary stage students - AZZAIZIA, Nassima (Art Law and Accounting Reporter, 2025)
This study aimed to attempt to identify the most important factors affecting the improvement of communication between the physical education and sports teacher and primary stage students, from the perspective of subject teachers in the province of Souk Ahras. We reached the following conclusions: scientific qualifications, the extent to which the physical education and sports teacher is familiar with child psychology, and his pedagogical experience significantly influence his interaction and communication with his students. In addition, an improvement in the teacher’s communication skills and an increased command of listening skills play a major role in enhancing and activating this communication.
Keywords: communication; physical education and sports teacher; primary stage